2008
DOI: 10.1111/j.1742-4658.2008.06287.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of the transcriptome and signal pathways in hepatic differentiation of human adipose mesenchymal stem cells

Abstract: The specific features of the plasticity of adult stem cells are largely unknown. Recently, we demonstrated the hepatic differentiation of human adipose tissue-derived mesenchymal stem cells (AT-MSCs). To identify the genes responsible for hepatic differentiation, we examined the gene expression profiles of AT-MSC-derived hepatocytes (AT-MSC-Hepa) using several microarray methods. The resulting sets of differentially expressed genes (1639 clones) were comprehensively analyzed to identify the pathways expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 37 publications
3
46
0
2
Order By: Relevance
“…During the embryonic development stage, Twist plays a vital role in hepatocyte differentiation, mainly in mesoderm development, a part of EMT [13,19]. However, uncontrolled and overexpressed Twist contributes to HCC development.…”
Section: Abnormal Twist Expression In Hcc Progressionmentioning
confidence: 96%
“…During the embryonic development stage, Twist plays a vital role in hepatocyte differentiation, mainly in mesoderm development, a part of EMT [13,19]. However, uncontrolled and overexpressed Twist contributes to HCC development.…”
Section: Abnormal Twist Expression In Hcc Progressionmentioning
confidence: 96%
“…There are many studies using HGF and EGF in the hepatocyte inducing protocol, and the concentrations of HGF and EGF showed wide ranges (Snykers et al 2009). The concentration of HGF ranges from 20 ng/ml to 150 ng/ml (Banas et al 2007;Kazemnejad et al 2008;Talens-Visconti et al 2006;Yamamoto et al 2008), and the concentration of EGF ranges from 10 ng/ml to 50 ng/ml (Kazemnejad et al 2008;Lange et al 2005;Shi et al 2005). Wang et al (2004) induced isolated BMMSCs with HGF in vitro at a concentration of 50 ng/ml, which mimicked the injured liver microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, most of the research work that can be found on ASCs is based on previous studies on BM-MSCs [11]. ASCs have also a great differentiation potential, demonstrated by a number of studies that have shown their neurogenic [1,12,13], cardiomyocyte and myocyte [14][15][16][17], endothelial cells [1,15], hepatocytes [18,19], adipogenic [1,20,21], and of course osteogenic and chondrogenic differentiation potential [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%